Preparation and Spectroscopic Studies of New Transition Metal Complexes of 1-(2, 2-Dicyclohexylethyl)-3-(1, 5-Dimethyl-3-Oxo-2-Phenyl-2,3-Dihydro-1H-pyrazol-4-ylimino) Indolin-2-One - Al-Hamdani, Abbas Ali Salih; Sadiq, Amal S; Mahmood, Tamador A (Al-Nahrain Journal of Science, 2018)
New tridentate ligand 1-(2, 2-dicyclohexylethyl)-3-(1, 5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-ylimino)indolin-2-one (L) was synthesized from the reaction of 3-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-ylimino)indolin-2-one and dicyclohexyl amine. Monomeric complexes of this ligand, of general formulae [VOII(L)(SO4)], [MIII(L)Cl3] with M=CrIII and FeIII, and [MII(L)Cl]Clwith (M = MnII and CoII) are reported. The mode of bonding and overall geometry of the complexes were determined through FT-IR, UV–Vis, and mass spectral studies, magnetic moment measurements, elemental analysis, metal content, chloride containing and molar conductance. These studies revealed octahedral geometries for the FeIII, CrIII complexes, square pyramidal for VO(II) complex and tetrahedral for the MnII and CoII complexes. The study of complexes formation via molar ratio and job method in DMF solution has been investigated and results were consistent to those found in the solid complexes with a ratio of (M:L) as (1:1). Hyper Chem-8 program has been used to predict structural geometries of compounds in gas phase the heat of formation (ΔHf º), binding energy (ΔEb), total energy, electronic energy and dipole moment at 298ok.